Prevalência do polimorfismo C3435T no gene MDR1 e sua associação com câncer de mama em mulheres de Mato Grosso, Brasil - Farina, Aguiar (2014)
Breast cancer (BC) is one the most common malignancy with high incidence and mortality worldwide, cancer exclusively female. Identify patients at higher risk for the disease, early diagnosis and institute immediate therapy has been identified as effective measures to reduce the mortality. Studies report association of C3435T polymorphism of MDR1 gene with CM without a clear demonstration of how this happens. Studies have reported that the presence of this T genotype associated with lower expression of MDR1 leading to lower effectiveness of the mechanism of efflux pump P - glycoprotein in the cell membrane, less disposal of toxic and carcinogenic agents out of the cell, the accumulation of carcinogens in intracellular environment could cause DNA damage and cancer. The present study aims to investigate the C3435T MDR1 gene polymorphism and its association with CM in women of Mato Grosso, Brazil. The epidemiological study design was case-control, peripheral blood samples from 201 patients and 177 controls seen at a referral oncology and breast Mato Grosso services were genotyped by PCR-RFLP for the C3435T polymorphism. The frequency of genotypes, adding controls and patients, CT was 52%, 30 % and 18 % CC and TT allele frequency was 56 % for the C allele and 44 % for allele T. Comparing patients and controls showed no statistical difference between the genotype frequencies and allelic. Found 30.3 % CC, 50.2 % CT and 19.4 % TT in patients and 29.9 % CC, 57.3 % CT and 16.4 % TT in the control group. These frequencies are similar to those found in the literature. There was no difference in genotype frequency compared with ethnicity. We conclude that the distribution of the C3435T polymorphism in the MDR1 gene was not associated with breast cancer or with ethnicity in this population sample.